Material Relations : The Marriage Figurines of Prehispanic Honduras - Hendon, Julia A. (Julia Ann); Lopiparo, Jeanne; Joyce, Rosemary A., 1956- (Book collections on Project MUSE., 2014)
"Focusing on marriage figurines--double human figurines that represent relations formed through social alliances--Hendon, Joyce, and Lopiparo examine the material relations created in Honduras between AD 500 and 1000, a period of time when a network of social houses linked settlements of a variety of sizes in the region. The authors analyze these small, seemingly insignificant artifacts using the theory of materiality to understand broader social processes. They examine the production, use, and disposal of marriage figurines from six sites--Campo Dos, Cerro Palenque, Copán, Curruste, Tenampua, and Travesia--and explore their role in rituals and ceremonies, as well as in the forming of social bonds and the celebration of relationships among communities. They find evidence of historical traditions reproduced over generations through material media in social relations among individuals, families, and communities, as well as social differences within this network of connected yet independent settlements. Material Relations provides a new and dynamic understanding of how social houses functioned via networks of production and reciprocal exchange of material objects and will be of interest to Mesoamerican archaeologists, anthropologists, and art historians"--